PERENCANAAN PENDIDIK DAN TENAGA KEPENDIDIKAN BERKARAKTER ISLAM DI LEMBAGA PAUD TK AN NASH JAKARTA - Sari, Anggita; Mujahidin, Endin; Andriana, Nesia (Generasi Emas, 2024)
The urgency of the need for teachers in the country is a problem that deserves special attention, especially in the recent period. The government's efforts to provide quality national education have been hampered due to the disproportionate ratio of teachers and students. PAUD management in Indonesia is currently facing significant progress. This can be illustrated by the number of services provided based on the age level and character of the child. Human Resource Planning is an effort to regulate between the needs or demands of human resources and the availability of the human resources needed at the time and place that is needed in sufficient quantity and quality. In terms of the recruitment of educators and teaching staff in Islamic education institutions in general and PAUD institutions in particular, it is necessary to pay attention in the recruitment of prospective educators in addition to having basic competencies as educators and teaching staff but also having Islamic character both in terms of knowledge and its application in everyday life in the way of the sunnah taught by Rasulullah Saw. For educators who have joined Islamic educational institutions but still have deficiencies in Islamic character, training and studies can be provided that can improve the ability to read the Qur’an and also the Islamic worldview of educators and teaching staff.